2020
DOI: 10.1021/acs.jpcc.0c01309
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chiral Modifiers from Solution onto Supported Platinum Catalysts: The Effect of the Solvent, Other Coadsorbates, and the Support

Abstract: The adsorption from a solution of s-1-(1-naphthyl)­ethylamine (s-NEA), cinchonidine, and cinchonine on Pt/SiO2, Pt/Al2O3, and a Pt disk was probed in situ by infrared absorption spectroscopy. Adsorption on the supported catalysts shows similar behavior to that seen on flat polycrystalline Pt surfaces, with the adsorption geometry transitioning from the aromatic ring lying close to parallel to the metal surface at low coverages to a more tilted geometry at monolayer saturation. The extent of the adsorption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 108 publications
(203 reference statements)
3
18
0
Order By: Relevance
“…It should be noted that exposure to reaction conditions involves the addition of various factors that can also affect the adsorption geometry of the ligands and their interaction with the prochiral reactant. It was demonstrated that the surface adsorption of hydrogen, , solvent molecules, , coadsorption of modifiers, , and reactants can alter the reaction mechanism and the adsorption geometry of surface ligands. It cannot be excluded that similar factors will also modify the adsorption geometry of NHC ligands during the enantioselective α-arylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that exposure to reaction conditions involves the addition of various factors that can also affect the adsorption geometry of the ligands and their interaction with the prochiral reactant. It was demonstrated that the surface adsorption of hydrogen, , solvent molecules, , coadsorption of modifiers, , and reactants can alter the reaction mechanism and the adsorption geometry of surface ligands. It cannot be excluded that similar factors will also modify the adsorption geometry of NHC ligands during the enantioselective α-arylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…9,28 Thus, both the reaction rate and enantioselectivity strongly depend on the size of the Pt NPs and the exposed Pt sites. 11,12,29 To exclude size effects on the catalytic performance, Pt NPs of uniform size were synthesized using two different capping agents, PVP and PVA. TEM images of the Pt Although capping agents are useful for the size control of NPs, the adsorbed capping agents on the metal surface can block the active sites, significantly decreasing the catalytic performance of the nanocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be kept in mind that during asymmetric hydrogenation, that is, in the presence of substrate, product and solvent, further changes are expected. Previous experimental investigations showed that the enantiodifferentiation of cinchona-modified Pt can also be affected by the interaction of the adsorbed modifier with other reaction components, substrate, 62 solvent, 63,64 product, 65 and other coadsorbates. 64 Thus, the present calculations only mimic the coadsorption behavior of CD and hydrogen, that is, the stability and spatial orientation of CD after the chiral modification procedure and hydrogen admission.…”
Section: Coadsorption Of CD Involving H-transfermentioning
confidence: 99%
“…Previous experimental investigations showed that the enantiodifferentiation of cinchona-modified Pt can also be affected by the interaction of the adsorbed modifier with other reaction components, substrate, 62 solvent, 63,64 product, 65 and other coadsorbates. 64 Thus, the present calculations only mimic the coadsorption behavior of CD and hydrogen, that is, the stability and spatial orientation of CD after the chiral modification procedure and hydrogen admission. The behavior of adsorbed CD under reaction conditions is expected to be more complex due its interaction with the substrate, and possible interactions with solvent and product.…”
Section: Coadsorption Of CD Involving H-transfermentioning
confidence: 99%